Optimization of Pile Construction Sequence Using CFA Machines - Ammar, Omar Wael (AUC Knowledge Fountain, 2025)
In most construction projects with deep foundations, piling activities are critical to the project schedule and often fall on the critical path. The piling construction process requires a diverse range of resources, including equipment, materials, and skilful labour. Without carefully planning the construction process according to installation standards, there is a significant risk of time and cost overruns. These overruns are caused by inefficiencies such as equipment idle or lost time due to required lags between closely spaced piles. Therefore, it is essential to develop an optimized construction sequence to minimize these risks and enhance overall project efficiency. The primary objective of this research is to develop a tool that schedules & optimizes the construction piling sequence to minimize the duration to complete the piles. Therefore, the optimization shall lead to enhanced resource usage and reduce the associated resource costs, particularly those incurred from equipment rentals. The research methodology involves developing a genetic algorithm code that incorporates time-space constraints to model the temporal lags between piles in proximity. The outcome of using the tool is a schedule that establishes an effective construction plan by providing an optimized construction sequence and a resource utilization schedule which enhances project efficiency and cost-effectiveness. The work presented in this study contributes to the literature of specialized scheduling techniques in the construction industry, as it allows practitioners to utilize a framework that identifies an optimum piling schedule that abides by time-space constraints. This can also benefit the construction industry as the framework provides useful resource usage data that could contribute into the creation of the budgeting and resource management plans for contractors, thus contributing to the successful management of a project.